Pioneering Hip: San Francisco and its Mid-Century Countercultures. - Uppenkamp, Molly. (2017)
Abstract: This thesis investigated the history of San Francisco and how it fostered the development of counterculture movements in the 1950s and 1960s. San Francisco, from its origins as a gold rush boomtown to modern movements of community preservation, has always been more encouraging of alternative viewpoints than other American cities. In the 1950s, San Francisco attracted migrants who expressed their dissatisfaction with American society through poetry and literature; this group of artists, led by Jack Kerouac and Allen Ginsberg, became the Beat Generation. As conformity became increasingly frustrating for a growing number of American young people, San Francisco was again the center of youth rebellion in the 1960s. The Hippie counterculture situated in Haight-Ashbury in the 1960s reflected continuity of counterculture ideals from the Beats of the 1950s. The development of these two countercultures in mid-century America was essentially facilitated by San Francisco's historically exceptional urban identity of nonconformity.; Thesis (M.A.)--Tufts University, 2011.; Submitted to the Dept. of History.; Advisor: Reed Ueda.; Committee: Ronna Johnson, and Virginia Drachman.; Keyword: American History.